PENERAPAN MODEL INKUIRI DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Imwarnita, Imwarnita (JURNAL SINEKTIK, 2020)
This study aims to improve the learning outcomes of science subjects about the relationship between special characteristics possessed by animals and plants using the inquiry model in grade VI at elementary school number 18 / IX Rengas Bandung. The method used in this research is action research with type of classroom action research consists of two cycles and with two meetings of each cycles, the time of this study is semester 1 of the 2019/ 2020 school year, with subjects in class VI consisting of 13 men and 13 women. Data collection techniques using observation and formative test results were analyzed by comparing the average score. The success criteria are individual KKM at 65, and classical at 80%, The results showed that pre-cycle learning completeness by 15% increased to 62% in cycle I and increased again to 92% in cycle II. teacher activity by 65% in cycle I increased to 80% in cycle II, student activity by 60% in cycle I increased to 78% in cycle II, Thus, it was concluded that the application of the inquiry model could improve the learning outcomes of science in terms of the relationship between the special characteristics possessed by animals and plants in grade VI students in Elementary School number 18 / IX Rengas Bandung.